VALIDITY AND RELIABILITY OF VIETNAMESE VERSION OF CYBERBULLYING COPING STYLES SCALE FOR STUDENTS - Thi Truc Quynh Ho; Chuanhua Gu (Tạp chí Khoa học Đại học Đà Lạt)
Based on the self-report coping scale (22 items) of Kochenderfer-Ladd and Skinner (2002), we have established and tested the validity and reliability of a Vietnamese version of the cyberbullying coping styles scale for students. The sample is 162 students from Hue University. Item discrimination analysis, item analysis, exploratory factor analysis, confirmatory factor analysis, and internal consistency reliability analysis were performed to assess the reliability and validity of the scale. The results show that the Vietnamese version of the cyberbullying coping styles scale had 21 items and 5 dimensions (problem solving, cognitive distance, looking for social support, externalization, and internalization). Analysis results showed that the Vietnamese version of the cyberbullying coping styles scale has good reliability and validity.